Reasoning over Large Semantic Datasets - De Virgilio, R; Orsi, G; Tanca, L; Torlone, R (2009)
This paper presents NYAYA, a flexible system for the management of Semantic-Web data which couples an efficient storage mechanism with advanced and up-to-date ontology reasoning capabilities. NYAYA is capable of processing large Semantic-Web datasets, expressed in a variety of formalisms, by transforming them into a collection of Semantic Data Kiosks that expose the native meta-data in a uniform fashion using Datalog+/-, a very general rule-based language. The kiosks form a Semantic Data Market where the data in each kiosk can be uniformly accessed using conjunctive queries and where users can specify user-defined constraints over the data. NYAYA is easily extensible and robust to updates of both data and meta-data in the kiosk. In particular, a new kiosk of the semantic data market can be easily built from a fresh Semantic-Web source expressed in whatsoever format by extracting its constraints and importing its data. In this way, the new content is promptly available to the users of the system. The approach has been experimented using well known benchmarks with very promising results.